Executive performance is related to regional gray matter volume in healthy older individuals. Issue 12 (19th July 2012) - Ruscheweyh, Ruth; Deppe, Michael; Lohmann, Hubertus; Wersching, Heike; Korsukewitz, Catharina; Duning, Thomas; Bluhm, Saskia; Stehling, Christoph; Keller, Simon S.; Knecht, Stefan
<x xml:space="preserve">Abstract</x> Individual differences in executive functioning and brain morphology are considerable. In this study, we investigated their interrelation in a large sample of healthy older individuals. Digit span, trail‐making, and Stroop tasks were used to assess different executive subfunctions in 367 nondemented community‐dwelling individuals (50–81 years). Task performance was analyzed relative to brain structure using voxel‐based morphometry, corrected for age and sex. Improved task performance was associated with increased local gray matter volume in task‐specific patterns that showed partial, but not complete overlap with known task‐specific functional imaging patterns. While all three tasks showed associations with prefrontal gray matter volume as expected for executive functioning, the strongest overlap between the three tasks was found in insular cortex, suggesting that it has a previously underestimated role for executive functions. The association between the insular cortex and executive functioning was corroborated using stereological region‐of‐interest measurement of insular volume in a subgroup of 93 subjects. Quantitatively, the volume of the single most strongly related region explained 2.4 ± 1.1% of the variance in executive performance over and above the variance explained by age, which amounted to 7.4 ± 4.1%. The age‐independent peak associations between executive performance and gray matter described here occurred in regions that were also strongly affected by age‐related gray matter atrophy, consistent with the hypothesis that age‐related regional brain volume loss and age‐related cognitive changes are linked. Hum Brain Mapp 34:3333–3346, 2013. © 2012 Wiley Periodicals, Inc.